PROBLEM BASED LEARNING DENGAN STRATEGI MIND MAP PADA MATERI EKOSISTEM UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Ucun Radi Muharam; Prasetyorini .; Dadang Jaenudin (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
PROBLEM BASED LEARNING WITH A MIND MAP STRATEGY ON ECOSYSTEM MATERIALS TO IMPROVE STUDENT LEARNING OUTCOMESThis study aims to describe the improvement of student cognitive, affective and psychomotor learning outcomes in ecosystem material, teacher and student learning activities, and student responses in the learning process using the Problem Based Learning model with mind map strategies. The study was conducted at Cianjur District PGRI Pagelaran Junior High School. This study involved 29 students in the experimental class and 30 students in the control class. The research method used was quasi-experimental with only test post design design. Data collection techniques use multiple choice tests for cognitive learning outcomes, questionnaires for affective students care about the environment, and product evaluation and performance for psychomotor. The results of the study using the problem based learning model with mind map strategies can improve the cognitive learning outcomes of students with a significance value of 0,000 0,05, students' caring attitude towards the environment includes a good category with a percentage of 83%, student skills in making mind maps including medium and high with the percentage of 61% and 39% respectively, and student discussion skills included sufficient and good categories with a percentage of 33% and 67% respectively. Learning with problem based learning models with mind map strategies provides opportunities for students to find solutions to the problems given. Problem based learning with mind map strategies can improve student cognitive, affective and psychomotor learning outcomes.